Depositional setting of the 2·1 Ga Francevillian macrobiota (Gabon): Rapid mud settling in a shallow basin swept by high‐density sand flows. Issue 3 (1st November 2017) - Reynaud, Jean‐Yves; Trentesaux, Alain; El Albani, Abderrazak; Aubineau, Jérémie; Ngombi‐Pemba, Lauriss; Guiyeligou, Grace; Bouton, Pascal; Gauthier‐Lafaye, François; Weber, Francis
Abstract: The depositional setting of the 2·1 Ga fill of the Franceville Basin of Gabon is important for understanding the habitat (energy and availability of light and oxygen) and taphonomy of recently discovered early macro‐organisms buried in black shales in Unit FB. The available data bearing on the stratigraphy and sedimentology of Unit FB provide new insight into processes acting on the palaeo‐sea floor. The shales are interpreted to have formed as fluid mud deposits interstratified with structureless sands. The latter (Poubara sandstones) were emplaced during a forced regression during the terminal infill of fault‐bounded sub‐basins following a stage characterized by a ferruginous to anoxic water column. The structureless sandstones were deposited from high‐density gravity currents along with a locally strong bottom oscillation of the water column. Tuft structures preserved in cyanobacterial mats, together with the position of the macro‐organisms at the top of the sandstone beds within associated black shales, point to a water depth of less than 80 m. The relative sea‐level fall that drove deposition of the Poubara sandstones controlled the rise of a phototrophic ecosystem and also possibly favoured the supply of oxygen and nutrients via density flows.